Mauritius : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper develops a Financial Conditions Index (FCI) for Mauritius-an instrument to gauge the operational state of the financial sector and predict real economy activity. The evolution of Mauritius' financial services sector has been supported by a vibrant offshore corporate sector. Given the strong macro-financial linkages, it is imperative to closely monitor domestic financial developments. Financial developments are broader than monetary developments depicting money supply and interest rates. The FCI is a robust predictor of real GDP growth in Mauritius. The FCI can also help inform macroprudential policy decisions. Decisions on setting the countercyclical capital buffer of Basel III could be informed by analyzing developments in the FCI. As historically Mauritius has not experienced drastic swings in financial credit, testing the constructed FCIs for predicting boom-bust episodes is difficult. Nevertheless, the FCI signaled lax financial conditions in 2009 and again in 2012 that likely contributed to accelerated credit growth in 2012-2013 and a subsequent acceleration in nonperforming loans during 2014-2016.